Sosialisasi Pelaksanaan Kegiatan Latihan Dasar Kepemimpinan Taruna (Ldkt) Sebagai Wahana Membentuk Jiwa Kepimpinan Pada Batalyon Taruna Akademi Maritim Nusantara Banjarmasin - Kamsariaty Kamsariaty (Greenation Publisher & Yayasan Global Resarch National, 2024)
Implementation of Basic Cadet Leadership Training (LDKT) activities at the Nusantara Maritime Academy Banjarmasin Rengat can have a very positive impact, especially in growing and developing a spirit of leadership and independence among cadets. The targets for implementing Basic Leadership Training (LDKT) are Cadets and the Rengat Cadet Battalion STAFF organization to prepare themselves when they enter society, how to face problems, understand various kinds of human characters, be self-disciplined, critical, independent, and become a leader so that to form professional cadets with a leadership mentality who have a critical, creative, initiative, proactive, broad-minded, integrated personality based on honesty, truth, and justice